Prevention of Perinatal Hepatitis B Virus Transmission in an Obstetric/Infant Population - Paul J Parker; Theresa W Gyorkos; Joseph S Dylewski; Arvind K Joshi; Elaine D Franco (Canadian Journal of Infectious Diseases)
Study Design: This retrospective study reviewed the screening practice and seroprevalence of hepatitis B surface antigen (HBsAg) among all mothers with live births at a teaching hospital in Montreal between November 1, 1990 and April 30, 1991.